The Effect of Health Promotion with Pop-Up Book Media on Elementary School Students' Knowledge and Practice of Dental Caries Prevention - Rositian, Ade Melia; Musthofa, Syamsulhuda Budi; Nurjazuli, Nurjazuli (Journal La Medihealtico, 2024)
Caries or cavities and gum problems are the most common oral diseases in children. As many as 89% of children in Indonesia under the age of 12 suffer from oral diseases. Learning about dental health in children has received less attention, and one of the causes is the method used so far is still with lectures, children are less interested and feel bored, so learning outcomes are not optimal. This study aims to analyze the effect of dental health promotion using Pop Up Book media on knowledge and practice of preventing dental caries in elementary school students. This study used a quasi-experiment with two groups consisting of one experimental group and one control group. The results of the study on the knowledge and practice of preventing dental caries of students with Pop Up Book media for the pre test and post test showed positive students experienced an increase in student practice by using Pop Up Book media from the pre test value to the post test value. So it can be concluded that there is an effect of Pop Up Book media on students' knowledge and practice of brushing teeth in an effort to prevent dental caries.